KARAKTERISTIK PERUSAHAAN DAN KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi pada Perusahaan Manufaktur Sektor Logam dan Sejenisnya di Bursa Efek Indonesia) - Atmoko, Daru Setio; Titisari, Kartika Hendra; Suhendro, Suhendro (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study discusses company size, profitability, leverage, liquidity, ownership structure, and the board of commissioners regarding the timing of financial reporting. The population and sample in this study are manufacturing companies in the metal sector and the like listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling technique of this study used purposive sampling technique. The number of samples in this study were 15 metal sector manufacturing companies and the like listed on the Indonesia Stock Exchange in the 2014-2018 period. The data analysis technique used in this study is logistic regression. Based on the results of the analysis conducted shows the size of the company, ownership structure, and board of commissioners related to the timeliness of financial reporting. While profitability, leverage, and liquidity do not affect the timeliness of financial reporting.